Dual fuel combustion and hybrid electric powertrains as potential solution to achieve 2025 emissions targets in medium duty trucks sector. (15th November 2020) - García, Antonio; Monsalve-Serrano, Javier; Martinez-Boggio, Santiago; Gaillard, Patrick; Poussin, Olivier; Amer, Amer A.
Highlights: Parallel hybrid architecture evaluated for different trucks and engine maps. CO2 2025 levels with ultra-low NOx and soot emissions for different truck versions. Cost function to evaluate the battery cost and European CO2 penalties. Battery cost considered for 2020 and 2025 scenarios. Abstract: The European commission is targeting a 15% reduction in CO2 emissions for medium and heavy-duty transportation starting in 2025. Moreover, the next European normative (EU VII) will impose a decrease of 50% for NOx and particulate matter emissions with respect to the current EUVI normative. Meeting these requirements pose a significant challenge to truck and bus manufacturers. Several proposals appeared in the last few years as improve the cabin aerodynamics, decrease the friction losses and improve the powertrain efficiency. The last point involves improving the current combustion systems as well as the transmission and energy management. This work proposes to couple two potential technologies to reduce at the same time the global (CO2 ) and local pollution (NOx and soot). For this, two truck platforms representative of medium-duty applications (18 ton and 25 ton) are tested using the reactivity controlled compression ignition (RCCI) combustion mode with diesel and gasoline as fuels. In addition, the trucks are electrified to full hybrid technology in a parallel pre-transmission (P2) architecture. A 0D vehicle numerical model is used to evaluate the trucks under four different driving cycles representative of homologation and real driving conditions. The numerical model is validated against on road measurements. The RCCI combustion is modeled by means of a map-based approach with 54 points measured in steady-state conditions. This work presents a complete engine map calibration with measurements up to 350 hp using two combustion modes inside the map (so-called dual-mode dual-fuel). As a baseline, the commercial diesel no-hybrid trucks and the dual-fuel no-hybrid trucks are used. The results show the potential of the dual-mode dual-fuel combustion to achieve ultra-low NOx and soot emissions. In addition, the CO2 target reduction is achieved for several truck platforms and driving conditions due to the hybridization of the driveline. The cycles with large phases of urban driving are the most favorable due to the ability of recovering energy by means of the regenerative braking system and the possibility to avoid large idling phases with respect to the no-hybrid versions. In addition, the decrease of the payload improves the CO2 reduction with respect to the baseline cases.